Time analysis of wireless controller area network-based fire and gas safety system. (2017) - Mary, Gerardine Immaculate; Alex, Zachariah C.; Jenkins, Lawrence
Fire and gas safety (FGS) system are important tools for safeguarding process plants and production facilities that handle flammable and toxic materials. In general, a conventional fire and gas system has several shortcomings, such as weakness to noise and false alarms. In order to overcome these shortcomings, controller area network (CAN)-based FGS system has been implemented in our previous work. Further, considering that FGS systems are employed in hazardous environments, where wireless implementation of CAN is desirous, an attempt to make CAN wireless is carried out for these systems in this work, by using the radio protocol IEEE 802.15.4 to communicate CAN messages wireless. This work is a continuation of our previous work. Here the wired CAN interface is converted to wireless CAN and response time analysis of the system is done using CANoe v7.6.